2011
DOI: 10.1103/physreva.84.052710
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg-atom formation in strongly correlated ultracold plasmas

Abstract: In plasmas at very low temperatures formation of neutral atoms is dominated by collisional three-body recombination, owing to the strong ∼ T −9/2 scaling of the corresponding recombination rate with the electron temperature T . While this law is well established at high temperatures, the unphysical divergence as T → 0 clearly suggest a breakdown in the low-temperature regime. Here, we present a combined molecular dynamics-Monte-Carlo study of electron-ion recombination over a wide range of temperatures and den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 92 publications
(150 reference statements)
1
39
0
Order By: Relevance
“…Our experimental results were consistent with molecular dynamics modeling of our system. We report a measured electron strong coupling parameter as large as Γ = 0.35 (8), which demonstrates that experimental conditions at low density can achieve greater value of Γ than predicted in [24], consistent with other predictions [28,29]. In addition, we identify a previously unreported heating mechanism that occurs due to the presence of a DC electric field during UCP formation.…”
supporting
confidence: 86%
“…Our experimental results were consistent with molecular dynamics modeling of our system. We report a measured electron strong coupling parameter as large as Γ = 0.35 (8), which demonstrates that experimental conditions at low density can achieve greater value of Γ than predicted in [24], consistent with other predictions [28,29]. In addition, we identify a previously unreported heating mechanism that occurs due to the presence of a DC electric field during UCP formation.…”
supporting
confidence: 86%
“…Moreover they show a nontrivial dependence on n. These features cannot be attributed to Doppler or saturation effects since, for the given experimental parameters, they are in the order of 100 kHz. Furthermore it has been repeatedly demonstrated that the bulk excitation of Rydberg atoms in the ultracold regime rapidly leads to a series of secondary effects such as fast ionization by collisions or radiation [9,12], production of plasmas [13][14][15], or blockade effects [16,17]. In our case, on the time scale of the excitation these secondary effects are certainly present and a complete understanding of the observed features necessarily requires one to take into account all of them.…”
mentioning
confidence: 79%
“…(8). This is useful for plasmas that evolve from cold Rydberg gases, for example, where the initial electron temperature is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…These plasmas are typically generated by photo-ionizing lasercooled gases [1] or gases in an ultrasonic jet [2]. They are diagnosed using three-body recombination [3][4][5][6][7][8], thermalization rates [9][10][11][12], electron evaporation or rf absorption [3,[13][14][15][16][17][18], charged particle imaging and detection [2,19], and optical fluorescence [12,20,21] and absorption [22][23][24]. Theoretical calculations and simulations [25][26][27][28][29][30][31][32] give great insights into the properties of these plasmas.…”
mentioning
confidence: 99%